EFEKTIVITAS MODEL PEMBELAJARAN PROJECT-BASED LEARNING (PJBL) DALAM MENINGKATKAN PEMAHAMAN DAN MOTIVASI BELAJAR SISWA TENTANG HAK DAN KEWAJIBAN WARGA NEGARA INDONESIA (WNI) DI SMAN 21 SURABAYA - Estuningsih, Kristiwi; Satriyani, Deny Yuniar; Syarifuddin Arif; Yusuf Agung Bintoro (AL-MUADDIB: Jurnal Kajian Ilmu Kependidikan, 2025)
This study aims to analyze the effectiveness of the Project-Based Learning (PjBL) model in enhancing students’ understanding and learning motivation regarding the rights and obligations of Indonesian citizens (WNI) at SMAN 21 Surabaya. The research employed a quantitative approach with a quasi-experimental design using a pretest-posttest control group. The sample consisted of two classes: an experimental class applying the PjBL model and a control class using conventional teaching methods. Data were collected through comprehension tests, learning motivation questionnaires, and classroom activity observations. The results showed that the application of the PjBL model significantly improved students’ comprehension (p < 0.05) and learning motivation (p < 0.05) compared to conventional methods. These findings affirm that PjBL is an effective instructional strategy for enhancing conceptual understanding and student motivation in Civic Education, particularly on the topic of citizens’ rights and obligations.